Design and modeling of a periodic single-phase sandwich panel for acoustic insulation applications - Gazzola, Chiara; Caverni, Stefano; Corigliano, Alberto (Frontiers in Materials, 2022)
Sandwich and composite panels are widely adopted in acoustic applications due to their sound insulation properties that overcome mass-law-based partitions in the medium-high frequency regions. A key aspect in the design procedure of acoustic panels is the control of the resonance dominated region of the Sound Transmission Loss (STL) curve. Within that frequency range such systems usually show acoustic weakness and poor insulation performances with respect to standard single layer solutions. In the present contribution we want to highlight an innovative approach for the sandwich partitions concept. A novel single-phase sandwich panel is realized adopting a periodic repetition of a properly designed unit cell. The resulting internal truss structure is self-sustained and its mechanical stiffness can be tuned to maximize the STL in the resonance dominated region. A series of parametric analysis is reported to show how the topology of the unit cell affects the noise reduction properties of the panel. An experimental validation is performed on a Nylon 3D printed prototype. The proposed panel is then integrated with some Locally Resonant elements that can be adopted to further improve the low frequency STL of the solution. Industrial and production considerations are also taken into account during the design process to make the solution industrially valid with a circular economy focus.